Employment Effects of Early Interventions on Job Search Programs - Andrea Maria Weber; Helmut Hofer (Institute for the Study of Labor (IZA), 2004)
We investigate the dependence of the program effect on varying entry times for a low cost job-search assistance program in Austria. The Austrian targeting policy is to admit every unemployed to a job-search program before the fourth month. The program effect is measured by a shift in the transition rate into employment upon program entry, using the timing-of-events method. Our findings are that the program effect is positive and does not vary significantly for program entries during the first year of unemployment, but it drops drastically thereafter.
Keywords: C14; J64; C41; 330; active labour market policy; early intervention; treatment effect; multivariate duration model; Arbeitsuche; Arbeitsmarktpolitik; Berufliche Integration; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Österreich; treatment effect